Psychological safety as mediator of patient safety culture - Erick Evander; Hendra Achmadi; Timotius William Yusuf (Intelektual Pustaka Media Utama, 2026)
Preventable adverse events continue to undermine patient safety globally, yet the psychosocial pathways shaping safety culture remain poorly understood in non-Western hospital settings. This cross-sectional study examines how burnout, job stress, and perceived organizational support influence patient safety culture, with psychological safety as a mediating variable, among 347 healthcare professionals across three Type C hospitals in Jakarta, Indonesia. PLS-SEM results confirm that burnout (β = -0.293) and job stress (β = -0.323) significantly erode psychological safety, while perceived organizational support strengthens it (β = 0.440). Psychological safety, in turn, is the strongest predictor of patient safety culture (β = 0.468) and mediates all three antecedent relationships, with indirect effects of -0.137, -0.151, and +0.206 respectively. The model explains 46.5% of variance in patient safety culture. These findings identify psychological safety as the critical mechanism through which workplace conditions reach safety outcomes, and call for hospital interventions targeting supportive leadership, workload management, and non-punitive reporting environments.